Relações de identidade entre estímulos familiares de diferentes categorias em macacos-prego (Cebus cf. apella) - LOBATO, Suélen Nicole da Silva (Universidade Federal do Pará, 2014)
Assuming that teaching complex repertoires begins with teaching its prerequisites, controlling relationships in teaching two adult capuchin monkeys zero-delay identity matching to sample conditional discriminations of pictures of known items were investigated. The number of simultaneous choices was gradually increased as performance reached criterion of 90% of correct choices. Eva was first trained IDMTS with two simultaneous choices, then four relations of identity with only 2 comparisons in each trial, and finally four identity relations with four comparisons. Cotoh was first trained IDMTS with four stimuli and four comparisons per trial, then 8 relations and 8 comparisons per trial, and finally 16 relations and 16 comparisons, followed by a generalized identity test. Changes were contingent to reaching criterion of 90% correct trials for two sessions. Both participants eventually reached criterion in identity matching. Further than generalized identity, the male showed signs of category formation with new stimuli the second test. The use of familiar stimuli, the gradual increase in the number of identity relations and number of comparisons per trial seems to promote learning.